2018
DOI: 10.21815/jde.018.050
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Dental Students’ Reflections on Interprofessional Practice After a Service‐Learning Experience in Appalachia

Abstract: Nowhere is the discrepancy between good and poor oral health status more pronounced in the U.S. than in the Appalachian region, where there is a high incidence of dental problems related to non-flouridated water, limited access to care, and tooth loss. To address these disparities, in 2016 University at Buffalo dental and nurse practitioner faculty members led a group of dental and nursing students on a two-day service-learning experience in rural Tennessee. The aim of this study was to assess the dental and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 5 publications
(4 reference statements)
2
18
0
1
Order By: Relevance
“…The fact that both NP and dental students reached near‐perfect scores on the RIPLS scale in teamwork and collaboration after IPCE training suggests that students in this university's culture are being sensitized to the needs of patients. The findings are also similar to Nierenberg et al's recent study, which found that exposure of students to patients in areas with health inequities increased the students' appreciation of the need for interprofessional practice in meeting patient needs 17 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that both NP and dental students reached near‐perfect scores on the RIPLS scale in teamwork and collaboration after IPCE training suggests that students in this university's culture are being sensitized to the needs of patients. The findings are also similar to Nierenberg et al's recent study, which found that exposure of students to patients in areas with health inequities increased the students' appreciation of the need for interprofessional practice in meeting patient needs 17 …”
Section: Discussionsupporting
confidence: 89%
“…Simulation experiences have already been shown to improve attitudes of both dental/dental hygiene and NP students 10, 16 . In addition, service‐learning experiences exposing students to patients who lack dental care and have severe oral health problems were found to impact developing nursing and dental professionals in their future willingness to provide care in settings that serve patients with health and oral health inequities 17 . There is a dearth of published research assessing IPCE collaborations between NP and dental students while providing patient care.…”
mentioning
confidence: 99%
“…Seven of the 11 studies provided suggestions for including an oral health component in nursing curricula. Six of the seven studies [46][47][48][50][51][52] focussed on an interprofessional oral health education model. The remaining study [49] provided information about resources for older people's oral health care for nursing curricula.…”
Section: Need For Further Oral Health Care Education For Nursing Studmentioning
confidence: 99%
“…An interprofessional education (IPE) model in which nursing students work with, learn from, and contribute to the oral-systemic knowledge of dental and other allied health students has been found effective in improving understanding of nursing students towards their role in oral health care [46][47][48][50][51][52]. All the studies focussing on IPE were conducted in the US except the study by Grant et al [46], which was conducted in Canada.…”
Section: Value Of An Interprofessional Education Modelmentioning
confidence: 99%
“…It would be useful to compare our results with findings from other health professions concerning the frequencies with which these programs engage in IPE and with which disciplines they collaborate most often. However, while several studies have assessed students’ IPE‐related attitudes in dentistry, 25 29 medicine, 22 , 25 , 30 nursing, 27 , 31 33 and pharmacy, 26 , 29 the results of studies with program directors or deans are much less available. In 2012, Formicola et al published a survey of dental school deans 15 .…”
Section: Discussionmentioning
confidence: 99%